2022
DOI: 10.1097/j.pain.0000000000002614
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal sensory modulatory effects of galcanezumab and clinical response prediction

Abstract: Galcanezumab, a monoclonal antibody against calcitonin gene-related peptide, is an emerging migraine preventative. We hypothesized that the preventive effects are conveyed via the modulation of somatosensory processing and that certain sensory profiles may hence be associated with different clinical responses. We recruited migraine patients (n 5 26), who underwent quantitative sensory tests over the right V1 dermatome and forearm at baseline (T0), 2 to 3 weeks (T1) and 1 year (T12) after monthly galcanezumab t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Incorporating the concept that the baseline excitability and responsivity state of central trigeminovascular neurons (as reflected by enhanced sensitivity to skin stimulation) that mediate the headache phase of migraine could determine outcome of prophylactic treatment of migraine, Wang and his colleagues (11) reported recently that the prophylactic treatment of chronic migraine (CM) with the calcium channel blocker flunarizine was significantly more effective in those participants whose skin sensitivity to mechanical and thermal stimulation of the periorbital region was relatively normal, in comparison to those whose periorbital skin sensitivity was abnormally heightened. Somewhat similarly, May and colleagues (12) reported that the pre-treatment forearm heat pain threshold of migraine patients whose number of migraine days per month (MMD) decreased by >30% following a three-month period of galcanezumab treatment was significantly higher (45.2°C) than in those who failed to achieve the 30% reduction in MMD (44.3°C).…”
Section: Introductionmentioning
confidence: 91%
“…Incorporating the concept that the baseline excitability and responsivity state of central trigeminovascular neurons (as reflected by enhanced sensitivity to skin stimulation) that mediate the headache phase of migraine could determine outcome of prophylactic treatment of migraine, Wang and his colleagues (11) reported recently that the prophylactic treatment of chronic migraine (CM) with the calcium channel blocker flunarizine was significantly more effective in those participants whose skin sensitivity to mechanical and thermal stimulation of the periorbital region was relatively normal, in comparison to those whose periorbital skin sensitivity was abnormally heightened. Somewhat similarly, May and colleagues (12) reported that the pre-treatment forearm heat pain threshold of migraine patients whose number of migraine days per month (MMD) decreased by >30% following a three-month period of galcanezumab treatment was significantly higher (45.2°C) than in those who failed to achieve the 30% reduction in MMD (44.3°C).…”
Section: Introductionmentioning
confidence: 91%
“…This association was especially evident in cephalic allodynia (OR for ≥50% response: 0.037, 95% CI: 0.004-0.181), but was also seen with extra-cephalic allodynia (OR for ≥50% response: 0.188, 95% CI: 0.022-0.954). A higher heat pain threshold, which represents a lower sensitivity to thermal stimuli and predicted a good response to CGRP(-R) mAbs (OR for higher heat pain thresholds in • C: 2.57, 95% CI: 1.08-6.11), was found in another study [44]. In Pensato et al [68], the presence of allodynia as a clinical symptom was associated with nonresponse after 3 months of treatment with CGRP(-R) mAbs (OR for ≥50% response: 0.47, 95% CI: 0.24-0.94).…”
Section: Sensitizationmentioning
confidence: 73%
“…Of these, currently 77% have obtained an academic position, which in over half the cases involves headache. Ten former IHS fellows have published at least one first author paper in collaboration with the host institution, and several of these publications have been accepted in high impact journals ( 2 11 ). Figure 1 shows the country of origin and of destination of all recipients of the IHS Fellowship.…”
Section: Resultsmentioning
confidence: 99%